Please answer quickly for me
1 answer:
Answer:
f(x)⁻¹ = x³ + 2
Step-by-step explanation:
Find the inverse of f(x) = ∛(x - 2).
The first step is to let f(x) = y
y = ∛(x - 2)
Then make x the subject of the formula
y³ = [∛(x - 2)]³
y³ = x - 2
x = y³ + 2
∴ f(x)⁻¹ = y³ + 2
Replacing y with x we have.
f(x)⁻¹ = x³ + 2
You might be interested in
Answer:
3inches each month or 36inches in a year
Step-by-step explanation:
Answer:
it is a game
Step-by-step explanation:
Answer:
A. m = -6
Step-by-step explanation: